El arte moderno en Colombia en sus relaciones con la moral y la política: a propósito de la pintora Débora Arango - Rosas Gallego, Ana María (Sociedad y Economía, 2008)
This article examines some reactions ofart critics in Colombia, in the mid-1940s, on the works ofthe painter Debora Arango. Through this way, some reflections are made on the relationship among morality, politics and the art work, in a society and a certain moment, from the standpoint ofsociological analysis.